Turnitin as a Dual-Function Tool: Detection and Education in Academic Writing Practices - Wulandari, Wida; Canda Sakti, Norida; Nurlaili, Eka Indah; Irawan, Nico; Dwi Saputra, Maskhur (Educational Researcher Journal, 2025)
Plagiarism remains a major challenge in higher education, undermining academic integrity and scientific standards. This study explores the dual role of Turnitin as a detection tool and learning resource in promoting academic integrity and improving students' writing skills in Indonesia. Using a survey method on a proportional stratification sample of 91 students of the State University of Surabaya, this study analyzed students' perception of plagiarism and their experience using Turnitin. The results show a high awareness of plagiarism, but there is a significant gap in the understanding of correct citation practices, exacerbated by cultural and infrastructure challenges. Turnitin is seen as a valuable tool, especially when integrated within a broader pedagogical framework, but limited access and training hinder its full potential. The study highlights Turnitin's contribution to fostering academic ethics and its impact on writing quality, while also highlighting the need for a comprehensive education strategy to address fundamental challenges. Practical implications include recommendations for better integration of antiplagiarism software in curricula, training for lecturers, and policy development to build a culture of academic integrity.